Integrative analyses of morphology, physiology, and transcriptional expression profiling reveal miRNAs involved in culm color in bamboo - Zhu, Chenglei; Lou, Yongfeng; Yang, Kebin; Liu, Yan; Xiao, Xiaoyan; Li, Ziyang; Guo, Dong; Sun, Huayu; Gao, Zhimin (Frontiers in Plant Science, 2022)
Culm color variation is an interesting phenomenon that contributes to the breeding of new varieties of ornamental plants during domestication. De-domesticated variation is considered ideal for identifying and interpreting the molecular mechanisms of plant mutations. However, the variation in culm color of bamboo remains unknown. In the present study, yellow and green culms generated from the same rhizome of Phyllostachys vivax cv. Aureocaulis (P. vivax) were used to elucidate the molecular mechanism of culm color formation. Phenotypic and physiological data showed that environmental suitability was higher in green culms than in yellow culms. High-throughput sequencing analysis showed 295 differentially expressed genes (DEGs) and 22 differentially expressed miRNAs (DEMs) in two different colored bamboo culms. There were 103 DEM-DEG interaction pairs, of which a representative “miRNA-mRNA” regulatory module involved in photosynthesis and pigment metabolism was formed by 14 DEM-DEG pairs. The interaction of the three key pairs was validated by qPCR and dual-luciferase assays. This study provides new insights into the molecular mechanism of miRNAs involved in P. vivax culm color formation, which provides evidence for plant de-domestication and is helpful for revealing the evolutionary mechanism of bamboo.